Study on Noise Attenuation Characteristics of Hydrofoil with Specific Cavitation Number - XIAOHUI, He; ZHONGLE, Liu; CHAO, Yang; ZHIYONG, Yuan (Archives of Acoustics, 2023)
In this study, the modified Sauer cavitation model and Kirchhoff-Ffowcs Williams and Hawkings (K-FWH) acoustic model were adopted to numerically simulate the unsteady cavitation flow field and the noise of a three-dimensional NACA66 hydrofoil at a constant cavitation number. The aim of the study is to conduct and analyze the noise performance of a hydrofoil and also determine the characteristics of the sound pressure spectrum, sound power spectrum, and noise changes at different monitoring points. The noise change, sound pressure spectrum, and power spectrum characteristics were estimated at different monitoring points, such as the suction side, pressure side, and tail of the hydrofoil. The noise characteristics and change law of the NACA66 hydrofoil under a constant cavitation number are presented. The results show that hydrofoil cavitation takes on a certain degree of pulsation and periodicity. Under the condition of a constant cavitation number, as the attack angle increases, the cavitation area of the hydrofoil becomes longer and thicker, and the initial position of cavitation moves forward. When the inflow velocity increases, the cavitation noise and the cavitation area change more drastically and have a superposition tendency toward the downstream. The novelty is that the study presents important calculations and analyses regarding the noise performance of a hydrofoil, characteristics of the sound pressure spectrum, and sound power spectrum and noise changes at different monitoring points. The article may be useful for specialists in the field of engineering and physics.